USAGE AND IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE SYSTEMS IN ENTERPRISE MANAGEMENT: A COMPARATIVE ANALYSIS OF ECONOMIC FEASIBILITY IN UKRAINE AND WORLDWIDE - Drobotenko , А.; Zhuk , Є. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
This article provides a comprehensive comparative analysis of the adoption and use of artificial intelligence (AI) systems in enterprise management in Ukraine and leading economies worldwide. The relevance of the study is justified by the accelerating digital transformation of business, the growing need to enhance enterprise competitiveness, and the broader challenges of the global economy. The research advances and tests a hypothesis concerning the economic and organizational feasibility of implementing AI systems across a wide spectrum of enterprises. The methodological foundation of the study employs a mixed approach, integrating quantiative methods (statistical analysis of Eurostat, McKinsey Global Institute, and PwC datasets) with qualitative methods (examination of international business cases and corporate reports). Particular attention is devoted to legal and regulatory aspects of AI in business activities, including the European AI Act and Ukraine’s “White Paper” on AI regulation. The article also investigates the current state of AI adoption in Ukraine and other countries, illustrating its findings with successful case studies and quantitative measures of effectiveness. The analysis identifies key barriers impeding the implementation of AI systems in Ukrainian enterprises, particularly financial constraints, underdeveloped IT infrastructure, shortage of qualified personnel, and risks associated with the ongoing war. On the basis of a systematic review of international experience and emerging trends, the article develops practical recommendations for the phased introduction of AI systems. These include: the selection of priority business processes with high return-on-investment potential, the evaluation of effectiveness through pilot projects, staff training and the creation of internal competence centers, compliance with ethical principles, and preparation for anticipated regulatory requirements. The findings of the research hold both practical and policy relevance. They can inform the design of digital transformation strategies for Ukrainian enterprises and contribute to the development of state policy aimed at supporting innovative technologies.